2022
DOI: 10.3389/ijph.2022.1605028
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Vision in Chinese School-Aged Children Before and After COVID-19

Abstract: Objectives: To investigate the changes of vision, including the prevalence of myopia, hyperopia, poor vision, and the spherical equivalent refraction (SER), in school-aged children before and after the pandemic of Coronavirus Disease 2019 (COVID-19).Methods: A school-based vision screening study was performed on children in 133 primary schools in Wuhan. This study was conducted in 4 consecutive years (2018–2021).Results: A total of 468,094 children (936,188 eyes) were recruited, 255,863 (54.7%) were boys. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…This study is one of the few to investigate the progression and incidence of myopia among Chinese schoolchildren after school reopens in the post-COVID-19 pandemic period. Consistent with recently published studies, our results showed a high risk of myopia among Chinese schoolchildren in the post-COVID-19 pandemic period, which might be associated with the failure to change unhealthy lifestyles and eyesight habits developed during the pandemic 9–11. Several recent studies have also presented a significant decrease in mean SER among schoolchildren during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study is one of the few to investigate the progression and incidence of myopia among Chinese schoolchildren after school reopens in the post-COVID-19 pandemic period. Consistent with recently published studies, our results showed a high risk of myopia among Chinese schoolchildren in the post-COVID-19 pandemic period, which might be associated with the failure to change unhealthy lifestyles and eyesight habits developed during the pandemic 9–11. Several recent studies have also presented a significant decrease in mean SER among schoolchildren during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…However, these studies only provide evidence of changes in the distribution of refraction during the COVID-19 lockdown, so more research is needed on whether the lifestyles and eyesight habits developed during the COVID-19 lockdown still have an impact on the burden of myopia after the COVID-19 pandemic. To our knowledge, there are only three studies on myopia progression among Chinese schoolchildren in the post-COVID-19 pandemic period in Chengdu, Hangzhou and Wuhan, respectively 9–11. As there is a high variation across the regions of China, more longitudinal studies of myopia are still in urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…Girls, in general tend to spend more time indoor doing near work activities, rather than doing outdoor physical activities. This was supported by previous studies, which also mentioned an increase in myopia prevalence and progression appearing in girls during the pandemic [17,19,23,24] .…”
Section: Age and Gender On Myopia Progressionsupporting
confidence: 88%
“…Generally, when the refractive error difference between the two eyes is 0.25D, there will be a 0.5% difference in image size formed on the retina. Most scholars at home and abroad believe that when the refractive error difference between the two eyes is greater than 2.50D, which means that the difference in retinal image size between the two eyes exceeds 5%, it will affect binocular fusion function and lead to decreased stereoscopic acuity [9][10][11]. Many patients in clinical practice with refractive error less than 2.50D also experience varying degrees of decreased stereoscopic acuity.…”
Section: Introductionmentioning
confidence: 99%